Phylogenetic and Functional Diversity of Saprolegniales and Fungi Isolated from Temperate Lakes in Northeast Germany - Hossein Masigol; Jason Nicholas Woodhouse; Pieter van West; Reza Mostowfizadeh-Ghalamfarsa; Keilor Rojas-Jimenez; Tobias Goldhammer; Seyed Akbar Khodaparast; Hans-Peter Grossart (Journal of Fungi, 2021)
The contribution of fungi to the degradation of plant litter and transformation of dissolved organic matter (humic substances, in particular) in freshwater ecosystems has received increasing attention recently. However, the role of Saprolegniales as one of the most common eukaryotic organisms is rarely studied. In this study, we isolated and phylogenetically placed 51 fungal and 62 Saprolegniales strains from 12 German lakes. We studied the cellulo-, lignino-, and chitinolytic activity of the strains using plate assays. Furthermore, we determined the capacity of 10 selected strains to utilize 95 different labile compounds, using Biolog FF MicroPlates™. Finally, the ability of three selected strains to utilize maltose and degrade/produce humic substances was measured. Cladosporium and Penicillium were amongst the most prevalent fungal strains, while Saprolegnia, Achlya, and Leptolegnia were the most frequent Saprolegniales strains. Although the isolated strains assigned to genera were phylogenetically similar, their enzymatic activity and physiological profiling were quite diverse. Our results indicate that Saprolegniales, in contrast to fungi, lack ligninolytic activity and are not involved in the production/transformation of humic substances. We hypothesize that Saprolegniales and fungi might have complementary roles in interacting with dissolved organic matter, which has ecological implications for carbon cycling in freshwater ecosystems.